PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) KOTA PEKANBARU - Kusdiana, Yayu (Sekolah Tinggi Ilmu Ekonomi Riau, 2018)
The Influence Of Leadership And Organizational Culture On Employee Performance On Regional Financial Management And Asset Board (BPKAD) Pekanbaru City. The purpose of this study to determine the influence of leadership and organizational culture on the performance of employees at the Regional Financial Management and Assets (BPKAD) Pekanbaru. The method in this research using quantitative descriptive method. This study uses a population of censuses, that is, the entire population is sampled. The sample in this research is 44. Hypothesis test consist of F test, and t test. Based on F test result proved that leadership and organizational culture have influence with significant level 0,00 to employee performance at BPKAD Pekanbaru City, indicated by value Fhitung bigger than Ftabel (69,841> 3,23). Based on t test proved that leadership has significant effect on employee performance at BPKAD Pekanbaru City shown by tcount bigger than ttabel (4,103> 2,01808) and organizational culture influenced with significant level 0,00 to employee performance at BPKAD Pekanbaru City indicated by value thitung is bigger than ttable (4,896> 2.01808).